Features of heart rate variability and heart rate in football referees of various qualification levels under competitive conditions - Kichkin, N.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the features of heart rate variability and heart rate in football referees of various qualification levels under competitive conditions. Methods and structure of the study. The study was conducted with football referees of various qualification levels who officiated matches of the Moscow City Championship and the Russian Championship among amateur football clubs. During pedagogical observations and pulse monitoring, heart rate and heart rate variability indicators were recorded for head referees and their assistants. A Polar H10 chest heart rate monitor was used for heart rate assessment, and the Elite HRV programme was used for heart rate variability analysis. Indicators were recorded before the match, during the game by pulse zones and after its completion. Results and conclusions. The obtained data indicate a higher level of functional stability in qualified referees and allow the consideration of heart rate and heart rate variability indicators as informative criteria for assessing the special preparedness of football referees.